Analysis of Risk and Mispricing Hypotheses of Accruals: Evidence from Brazil - Martins, Vinícius Gomes; do Monte, Paulo Aguiar; Machado, Márcio André Veras (Review of Business Management, 2018)
Purpose – Analyze how the accruals pricing is configured in the brazilian stock market, that is, if it represents a market mispricing or a risk factor. Design/methodology/approach – We used a sample of non-financial companies listed in B3. To reach the objective, the portfolio methodology, asset pricing models were used, and two-stage cross-sectional regression (2SCSR) was used to test risk and mispricing hypotheses. Findings – The results obtained showed evidence of the accruals anomaly for the companies classified as small and that the evidence is stronger when evaluating the discretionary component. The two-stage cross-sectional regression analysis did not show that accruals represent a risk factor, suggesting that the evidence of anomaly obtained for discretionary accruals is caused by mispricing. Originality/value – Non-rejection of the accruals’ mispricing assumption leads to the conclusion that stock prices of small firms are influenced by the accounting results disclosed and that managers, by having capital market and profit incentives related, can use accounting choices opportunists with the motivation to maximize their expected utility, that is, to influence the price of shares through the distortions in profits.